Functional characterization of a peptide fragment, Os(3-12), derived from the carboxy-terminal region of a defensin from the tick Ornithodoros savignyi - Gaspar, A.R.M. (Anabella Regina Marques) (University of Pretoria, 2015)
Dissertation (MSc)--University of Pretoria, 2016.